POTENSI SENYAWA TANNIN DALAM MENUNJANG PRODUKSI RAMAH LINGKUNGAN - Rani, Ismarani (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Tannin is the compound astringent, bitter plant polyphenols that contain groups that can form a complex hydrocyls strong links with proteins and other macromolecules.Tannins are water soluble phenolic compounds having molecular weights between 500 and 3000 Da that can bind and precipitate or shrink protein.Tannin classified intohydrolyzable tannins and condensed tannins (proanthocyanidins). Dekstruction or modification of tannin has an important role in wood preservatives, heavy metal adsorbents, medicine, antimicrobials, etc.